Total Benchmarking Sebagai Alat Menilai Kewajaran Laporan Keuangan Dan Pemenuhan Kewajiban Perpajakan - Bayu Sarjono (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2014)
AbstractThe objective of this research is to provide empirical evidence on the utilization of total benchmarking ratio as a mean to assess the fairness of financial statement and the fulfilment of tax obligation in financial intermediaries sector. Variables to be tested in this research are 14 ratio of benchmarking total consist of: Gross Profit Margin (GPM), Operating Profit Margin (OPM), Pretax Profit Margin (PPM), Corporate Tax to Turn Over Ratio (CTTOR), Net Profit Margin (NPM), Dividend Payout Ratio (DPR), Value-added Tax Ratio (pn), Salary/Sales Ration (g), Interest/Sales Ratio (b), Rent/Sales Ratio (s), Depreciation/Sales Ratio (py), Outside-business Revenue/Sales Ratio (pl), Outside-business Cost/ Sales (bl), Other-input/Sales Ratio (x). This research incorporates financial intermediaries sector because it has contributed to the 5 largest tax revenue in last 5 years. The research method used is descriptive qualitative method by calculating ratios then compare them to the benchmark set by the Directorate General of Taxes. The sample of this research is Business Field Classification (Klasifikasi Lapangan Usaha) in the financial intermediary sector: foreign exchange banks, insurance and consumer financing companies. The type of data used is secondary data, that is audited financial statements gathered form ICMD. The research results show that the largest ratio difference for foreign exchange banks and insurance companies is at interest expense; however, the largest ratio difference for consumer financing is at outside-business Costs.